MstH Is the Major High-Affinity Glucose Transporter with Pleiotropic Roles in Carbon Utilization Regulation and Citric Acid Production in Aspergillus niger - Zheng, Xiaomei; Chen, Meiling; Du, Peng; Cairns, Timothy C.; Zhang, Lihui; Gao, Kaiyue; Ni, Xiaomeng; Lei, Yu; Zheng, Ping; Sun, Jibin (Journal of agricultural and food chemistry, 2025)
Aspergillus niger is a versatile industrial workhorse for bulk biomanufacturing of organic acids and enzymic proteins owing to its remarkable capacity to utilize diverse crude carbon sources. Glucose, a primary carbon source, plays a critical role in industrial bioprocesses; however, the key components and mechanisms of its dual-affinity transport system in A. niger remain poorly characterized. Herein, we employed transcriptomic profiling and functional analysis of null mutants to comprehensively investigate the glucose transport system. We identified MstH as the principal high-affinity glucose transporter, surpassing MstA in importance, and demonstrated its collaboration with MstC under glucose-abundant conditions. Overexpression of MstH in A. niger significantly enhanced citric acid production by 41.94% compared to that of the parent strain. Furthermore, coexpression of MstH, MstC, and the citrate exporter CexA, along with the deletion of the byproduct-associated genes agdA (α-glucosidase) and oahA (oxaloacetate acetyl hydrolase), led to a citric acid titer of 155.87 ± 0.86 g/L, representing a 3-fold improvement. Transcriptomic analysis revealed that MstH overexpression downregulated the carbon catabolite repressor creA while activating the transcription factor amyR, resulting in upregulation of mstA and mstF and extensive derepression of amylolytic enzymes. Importantly, the point-mutated MstH variant MstHR156 K, with impaired transport function, retained its regulatory effects on creA and amyR, suggesting a moonlighting role for MstH in glucose uptake and carbon utilization regulation. These findings offer new insights into the underlying mechanisms of carbon source utilization and highlight the promising engineering targets for strain optimization in industrial biotechnology.